Dynamic behaviour of steel-concrete composite beams retrofitted with various bolted shear connectors. (15th January 2017) - Henderson, I.E.J.; Zhu, X.Q.; Uy, B.; Mirza, O.
Highlights: An experiment investigating retrofitting of novel shear connectors is presented. Damage accrued at incremental loading stages is examined with dynamic methods. An FEA is developed to further investigate the effects of retrofitting procedures. The dynamic behaviour of retrofitted specimens is different to cast-in specimens. Abstract: In structural engineering, composite construction has become increasingly widespread due to the improvement of mechanical properties it provides. Retrospective application of the composite construction principle to old structures may be beneficial. Many end of life structures are decommissioned and replaced. If the structural integrity of old structures could be improved their service life may be extended. Recently research on the development of post-installed or retrofitted shear connectors has been conducted. Most of the research in this area is concerned with modified versions of welded shear studs or various threaded rod and nut configurations, and refer to only one type of shear connector. Therefore, the suitability of the proposed models across differing shear connection types is unknown. An experimental study has been undertaken to ascertain the differences in dynamic behaviour of cast-in and retrofitted shear connectors using a series of identical steel-concrete composite beams with various shear connection systems. Two blind bolt connector types were used as shear connection systems in steel-concrete composite beams alongside a welded shear stud specimen in both cast-in and retrofitted configurations. A finite element model was then developed. The nature of changes in dynamic behaviour due to damage were investigated using the finite element model. It was found that at increased loading the behaviour of the cast-in and retrofitted connectors was fundamentally different due to the retrofitting procedure.